(untitled) (Impact: Journal of Transformation, 2022)
This paper examined how masculinity is constructed, how men view it, and how it is affected by domestic violence perpetrated against them by their wives in Bunyala Sub-County, Busia County Kenya. The paper is based on a study conducted in Bunyala Sub-County, Busia County, Kenya, on domestic violence against men and its implications on their perceived masculinity. It focuses on male victims of domestic violence within the Bunyala Sub-County. This paper attempts to answer whether domestic violence against men exists in Bunyala Sub-County, how masculinity is constructed in Bunyala Sub-County, what defines a man in Bunyala Sub- County and what are the implications of domestic violence against men (DVAM) on their perceived masculinity in Bunyala Sub-County. The paper employed mixed methods to gather quantitative and qualitative data through an exploratory research design. This study was guided by family conflict theory. Simple random sampling was utilized to come up with the study area. Gatekeepers, the village elders and assistant chiefs were nominated using purposive sampling while snowballing sampling was utilized to identify one hundred and one (101) men and women who were survivors or perpetrators of domestic abuse to participate in the stud. The paper focused on men and women who had been in marriages for at least five years and had or were experiencing domestic violence for at least one year. Information was gathered through interviews and focus group discussions using in-depth semi-structured interview schedules, focus group discussions and key-informant interview tools. The findings revealed diverse experiences of the effect of domestic violence against men, including stigmatization, discrimination, constant ridicule, denial of conjugal rights, and disrespect, among others. These findings provide important insights to stakeholders in helping to fight incidences of domestic violence in the community.